Aptamer-based Biosensor Developed to Monitor MUC1 Released by Prostate Cancer Cells - Karpik, Agnieszka E.; Crulhas, Bruno P. [UNESP]; Rodrigues, Carolina B. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (Wiley, 2017)
Electrochemical aptasensors can detect cancer biomarkers such as mucin 1 (MUC1) to provide point-of-care diagnosis that is low-cost, specific and sensitive. Herein, a DNA hairpin containing MUC1 aptamer was thiolated, conjugated with methylene blue (MB) redox tag, and immobilized on a gold electrode by self-assembly. The fabrication process was characterized by scanning electron microscopy, X-ray spectroscopy analysis and electrochemistry techniques. The results evidenced a stable and sensitivity sensor presenting wide linear detection range (0.65–110 ng/mL). Therefore, it was able to precisely detect MUC1 production patterns in normal (RWPE-1) and prostate cancer cells (LNCaP and PC3). The biosensor has ability to detect MUC1 in complex samples being an efficient and useful platform for cancer diagnosing in early stages and for physiological applications such as cancer treatment monitoring.
Keywords: aptamers; biomarkers; cancer; Electrochemical detection; protein monitoring